Hydrogen Sulfide and its Therapeutic Applications - Kimura, Hideo.; Kimura, Hideo. (Springer Vienna : Imprint: Springer, 2013)
The metabolism of sulfur especially by sulfurtransferases had been intensively studied in mid 1900’s.  Three enzymes, cystathionine β–synthase (CBS), cystathionine γ–lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (3MST) were found to have the capacity to produce H2S in vitro.  However, H2S was recognized simply as a by-product of the metabolic pathways or as a marker for evaluating the activity of enzymes rather than as a physiological active molecule.   In the late 1980’s relatively high concentrations of sulfide were measured in the brain that led to the successive studies of identifying the physiological functions of H2S.  Recently, the steady-state concentrations of H2S have been re-evaluated and found to be much less than that initially measured.  However, despite these differences, such re-evaluations served to further confirm the existence of H2S in mammalian tissues.  H2S is produced in almost every organ and plays various roles such as neuromodulation, vasodilation, insulin release, inflammation, angiogenesis and cytoprotection. The unregulated production of H2S and improper responses of target molecules are involved in the pathogenesis of various diseases.  This book focuses on these topics as well as on the recent progress in the biology and the therapeutic development of this molecule.